1997
DOI: 10.1073/pnas.94.24.13075
|View full text |Cite
|
Sign up to set email alerts
|

Multiple protein domains determine the cell type-specific nuclear distribution of the catalytic subunit required for apolipoprotein B mRNA editing

Abstract: Apolipoprotein B (apoB) mRNA editing catalyzed by apoB mRNA editing catalytic subunit 1 (APOBEC-1) has been proposed to be a nuclear process. To test this hypothesis, the subcellular distribution of hemagglutinin-(HA) tagged APOBEC-1 expressed in transiently transfected hepatoma cells was determined by indirect immunof luorescence microscopy. HA-APOBEC-1 was detected in both the nucleus and cytoplasm of rat and human hepatoma cells. Mutagenesis of APOBEC-1 demonstrated that the N-terminal 56 amino acids (1-56)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 49 publications
11
63
0
Order By: Relevance
“…AID dimerization through the β2 strand has been proposed based on the structure of A2 33 . We tested the effect of perturbing the predicted AID β2, residues [40][41][42][43][44][45][46][47][48][49][50][51][52][53] in our model, on oligomerization by introducing one (F46A), two (F46A/Y48A) 33 or four (F46A/Y48A/R50G/N51A, named AID FYRN) mutations. The ability of each of these mutants to interact with wt AID was monitored by comparing their efficiency in coimmunoprecipitating with AID-Flag.…”
Section: Aid Has a Conformational Positively Charged Nlsmentioning
confidence: 99%
See 1 more Smart Citation
“…AID dimerization through the β2 strand has been proposed based on the structure of A2 33 . We tested the effect of perturbing the predicted AID β2, residues [40][41][42][43][44][45][46][47][48][49][50][51][52][53] in our model, on oligomerization by introducing one (F46A), two (F46A/Y48A) 33 or four (F46A/Y48A/R50G/N51A, named AID FYRN) mutations. The ability of each of these mutants to interact with wt AID was monitored by comparing their efficiency in coimmunoprecipitating with AID-Flag.…”
Section: Aid Has a Conformational Positively Charged Nlsmentioning
confidence: 99%
“…Similarly to AID, the N-terminal domain of APOBEC1 is necessary but not sufficient for nuclear import 45,46 suggesting that APOBEC1 might also have a conformational NLS.…”
Section: Active Nuclear Import Of Aidmentioning
confidence: 99%
“…Several other auxiliary protein candidates have also been described that had binding affinities for APOBEC-1 and\or apoB mRNA and that demonstrated the ability to modulate editing efficiency [23,24,26,31,33,34,37,38]. Although, under biological conditions, editing occurs only in the nucleus [8,9], nuclear and cytoplasmic distributions have been described for both APOBEC-1 and ACF [9,52,53]. Nuclear editing has been characterized as occurring coincident with, or immediately after, pre-mRNA splicing [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that editing of all RNAs occurred in the nucleus ; however, we cannot rule out the possibility that editing of the unspliced apoB chimaeric RNA occured after it was exported to the cytoplasm. Although we have reported cytoplasmic localization of APOBEC-1 and ACF [9,52], there is no precedent for them to form active editosomes in the cytoplasm in i o or for there to be cytoplasmic editing when APOBEC-1 expression was under biological regulation [9]. Specifically, cytoplasmic APOBEC-1 and ACF existed within an inactive 60 S complex that only became an activated 27 S editosome in the nucleus [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…The apoB mRNA editing complex locates the apoB pre-mRNA among tens of thousands pre-mRNAs (12,13). No other mRNAs have been identified that are edited by this mechanism, and with the exception of a minor site in the human apoB mRNA, no other cytidines in the apoB mRNA are edited (14).…”
mentioning
confidence: 99%